The Effect of Alcohol on Blood Glucose Levels in Patients with Diabetes: A Systematic Review - Evans, Elizabeth (2008)
Introduction: Diabetes mellitus is a common condition affecting an estimated 180 million people worldwide, a figure that is set to double by 2030. Consumption of alcohol in young people in the UK has doubled in the last decade, leading to concern about the health and social consequences of increasing alcohol use.